Rethinking the Social and Solidarity Economy and Its Potential for Socio-Ecological Transitions: A Mesoeconomic Approach - Bodet, Catherine; Lamarche, Thomas; Richez-Battesti, Nadine (Revue Interventions économiques / Papers in Political Economy, 2026)
The article shows how the mesoeconomic approach can simultaneously account for the diversity of enterprises within the social and solidarity economy (SSE) and clarify the extent of their autonomy from the dominant accumulation regime. Mesoeconomics aims to shed light on arenas of production that maintain a degree of autonomy from the broader dynamics of accumulation. It thus allows us to grasp the endogenous diversity of capitalism and to observe how different meso arenas function, regardless of whether they remain marginal or succeed in scaling up to the broader accumulation regime. Our objective is to identify the possible contribution of the SSE to socio-ecological transitions grounded in its own internal logic.